2015
DOI: 10.1590/0074-02760150176
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-blind clinical trial of two yellow fever vaccines prepared with substrains 17DD and 17D-213/77 in children nine-23 months old

Abstract: This randomised, double-blind, multicentre study with children nine-23 months old evaluated the immunogenicity of yellow fever (YF) vaccines prepared with substrains 17DD and 17D-213/77. YF antibodies were tittered before and 30 or more days after vaccination. Seropositivity and seroconversion were analysed according to the maternal serological status and the collaborating centre. A total of 1,966 children were randomised in the municipalities of the states of Mato Grosso do Sul, Minas Gerais and São Paulo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…Similar results were found in an earlier study in which 71% of subjects seroconverted after two MVA immunizations but only 28.8% maintained neutralizing antibody responses by 2 months after booster vaccination [53]. In contrast to these viruses, in which the difference in host-pathogen interactions are clearly due to differences in vaccine strain attenuation, the vaccine strains of YFV-17D are genetically stable viruses [54] and show similar safety and immunogenicity profiles [2,46]. It is therefore unlikely that the long-lived immunity or short-lived immunity observed among different vaccinated individuals (Figure 2) is due to differences in vaccine virus strains.…”
Section: Yellow Fever Correlate Of Immunity and Duration Of Antibosupporting
confidence: 82%
See 3 more Smart Citations
“…Similar results were found in an earlier study in which 71% of subjects seroconverted after two MVA immunizations but only 28.8% maintained neutralizing antibody responses by 2 months after booster vaccination [53]. In contrast to these viruses, in which the difference in host-pathogen interactions are clearly due to differences in vaccine strain attenuation, the vaccine strains of YFV-17D are genetically stable viruses [54] and show similar safety and immunogenicity profiles [2,46]. It is therefore unlikely that the long-lived immunity or short-lived immunity observed among different vaccinated individuals (Figure 2) is due to differences in vaccine virus strains.…”
Section: Yellow Fever Correlate Of Immunity and Duration Of Antibosupporting
confidence: 82%
“…Importantly, seroconversion rates are also lower among children after YFV-17D vaccination (88% within 1–2 months after primary YFV-17D vaccination; [11]). A large clinical trial involving 1,966 children comparing 17D-213/77 and 17DD vaccines found seroconversion rates of only 84.8% and 85.8%, respectively [4]. However, among children aged 12 months or older, the seroconversion rate was only 69% when concomitant vaccination with measles, mumps, and rubella (MMR) was performed [4].…”
Section: Yfv Immunology Epidemiology and Evidence Of Waning Protementioning
confidence: 99%
See 2 more Smart Citations
“…Previous evidence suggested weaker immune response in specific groups, such as human immunodeficiency virus–infected people or infants 4. Specifically, vaccine efficacy in infants and children when coadministered with vaccination against measles, mumps, and rubella, has been recently questioned 20. These questions deserve further research effort.…”
Section: Discussionmentioning
confidence: 99%